Ultraviolet Number Counts of Galaxies from Swift Ultraviolet/Optical Telescope Deep Imaging of the Chandra Deep Field South - Hoversten, E.; Gronwall, C.; Vanden Berk, D.; Koch, T.; Breeveld, A.; Curran, Peter; Hinshaw, D.; Marshall, F.; Roming, P.; Siegel, M.; Still, M. (Institute of Physics Publishing, Inc., 2009)
Deep Swift UV/Optical Telescope (UVOT) imaging of the Chandra Deep Field South is used to measure galaxynumber counts in three near-ultraviolet (NUV) filters (uvw2: 1928 Å, uvm2: 2246 Å, and uvw1: 2600 Å) and the uband (3645 Å). UVOT observations cover the break in the slope of the NUV number counts with greater precisionthan the number counts by the Hubble Space Telescope Space Telescope Imaging Spectrograph and the GalaxyEvolution Explorer, spanning a range 21 mAB 25. Model number counts confirm earlier investigations infavoring models with an evolving galaxy luminosity function.